The Influence of Mass Media on the Criminal Justice Process in Minah’s Cocoa Theft Case: Pengaruh Media Massa Terhadap Proses Peradilan Pidana dalam Kasus Pencurian Kakao oleh Minah - Kurniawan Akbar (Unnes Law Journal, 2012)
In law enforcement, the media has a significant impact to the community through the preaching of a case. The mass media are able to create a public opinion on a matter of law with which it conveys information and news. Through public opinion in society, mass media perform the control functions of the judicial process of a lawsuit, not the exception in criminal cases. This study aims to analyze the influence of mass media on criminal justice processes in cases of theft of cocoa by Minah. The data used are the primary and secondary. The analysis used juridical-empirical approach. These results indicate that public opinion against theft case 3 (three) pounds of cocoa is one example of a control function that is run by the mass media. Mass media in this case highlights the criminal justice process is not fair for Minah. The influence of mass media appear in the proceedings against the defendant Minah by the panel of judges at the trial III, namely in terms of consideration of the verdict handed down by the judge against the defendant.